Profile of an occupation – technical product designer - Schambeck, Arne [Verfasser] (My University, 2024)
"Technical product designers conceptualise and develop data models, constructions, 3D models and components for everything from electric toothbrushes to mechanical diggers. This ensures that ideas and stipulations for products and machines can also be implemented. This profile presents tasks undertaken in both specialisms and figures relating to the occupation." (BIBB-Doku)
Keywords: S 6.3.2 Techniker, Technische Sonderkräfte, Zeichner, Industriemeister (ausgenommen IT-Berufe); 370; Technischer Produktdesigner; Berufsbeschreibung; Tätigkeitsmerkmal